The elasticity of substitution between clean and dirty energy with technological bias - Ara Jo (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
The elasticity of substitution between clean and dirty energy and the direction of technological change are central parameters in discussing one of the most challenging questions today, climate change. Despite their importance, there are few studies that empirically estimate these key parameters. In this paper, I estimate the elasticity of substitution between clean and dirty energy from micro data, jointly with technological parameters that reflect the direction of technological change within the energy aggregate. I find estimates of the elasticity of substitution ranging between 2 and 3. The largely dirty-energybiased technological change observed in the data validates the framework of directed technological change, given the historical movement of relative energy prices and the estimated elasticity of substitution above unity. However, I also find suggestive evidence that clean-energy-augmenting technology is growing faster than dirty-energy-augmenting technology in recent years with changes in relative energy prices and higher subsidies for clean energy.
Keywords: Q40; Q55; Q54; O33; 330; elasticity of substitution; directed technical change; climate change